Millennial Investment Decision Analysis - Reynard Jonathan; sumani sumani (Business and Entrepreneurial Review, 2021)
In managing finances, each aims to be able to generate income for himself. Investment is one of the individual decisions to increase the assets owned by allocating a certain amount of funds, time, and assets that are considered to generate returns. Millennial investors are the government's main target through financial literacy education that the Financial Services Authority has promoted in encouraging an increase in stock investment by the public. However, many factors influence investors to invest, including the environment and the investor's personal experience. The purpose of this study is to analyze the factors that influence the investment decisions of millennial private investors, including financial literacy, perceptions of risk and return, financial technology, family background, and income. The data taken for this study is primary data obtained through online questionnaires to people who are currently investing in the age range of 20-40. The number of samples of this study was 224 respondents through data collection using google form for two months. The research data were analyzed using SPSS 26 software. By using descriptive statistical data, validity and reliability tests, classical assumption tests such as autocorrelation, multicollinearity, heteroscedasticity. The results showed that financial literacy, perceptions of risk and return, financial technology, family background, and income influence millennial investor investment decisions. The implication of this result shows that parents should start to provide basic investment knowledge to teenagers as soon as possible, and the firm can invest more in financial technologies to serve young customers.